# Which shows the first step in the solution to the equation log_{2}x + log_{2}(x - 6) = 4?

**Solution:**

Given, the equation is log_{2}x + log_{2}(x - 6) = 4

We have to find the first step in the solution of the equation.

Using logarithmic laws,

log_{a}x + log_{a}y = log_{a}(xy)

Now, log_{2}x + log_{2}(x - 6) = 4 can be written as

log_{2} x(x - 6) = 4

Therefore, the first step is log_{2}x(x - 6) = 4.

## Which shows the first step in the solution to the equation log_{2}x + log_{2}(x - 6) = 4?

**Summary:**

The first step in the solution to the equation log_{2}x + log_{2}(x - 6) = 4 is log_{2} x(x - 6) = 4.

Math worksheets and

visual curriculum

visual curriculum